Quercetin Combined With Human Umbilical Cord Mesenchymal Stem Cells Regulated Tumour Necrosis Factor-α/Interferon-γ-Stimulated Peripheral Blood Mononuclear Cells via Activation of Toll-Like Receptor 3 Signalling - Chen, Guiling; Ye, Yang; Cheng, Ming; Tao, Yi; Zhang, Kejun; Huang, Qiong; Deng, Jingwen; Yao, Danni; Lu, Chuanjian; Huang, Yu (Frontiers in Pharmacology, 2020)
The beneficial effect of quercetin in rheumatic diseases is unclear. Studies have already confirmed that human umbilical cord mesenchymal stem cells (hUCMSCs) alleviate some symptoms of rheumatoid arthritis (RA) by their immunosuppressive capacities. This study explored whether there are additive effects of quercetin and hUCMSCs on peripheral blood mononuclear cells (PBMCs) under simulated rheumatic conditions. hUCMSCs were pretreated with quercetin (10 μM) before coculture with TNFα/IFN-γ-stimulated PBMCs at a ratio of 1:1 for 3 days. PBMC proliferation was inhibited, and the proportion of Th17 cells was shifted. These effects may be related to the effect of quercetin on functional molecules in hUCMSCs, including nitric oxide (NO), indoleamine 2,3-dioxygenase (IDO), interleukin 6 (IL-6) and Toll-like receptor-3 (TLR-3) and the Akt/IκB pathways. These results suggest that quercetin effectively promoted the immunoregulatory effect of hUCMSCs by inhibiting the Akt/IκB pathway, activating the Toll-like receptor-3 pathway, and regulating downstream cytokines.